Topographic change analysis and flood risk assessment in Jepara Regency, Indonesia, using GIS-based multi-criteria spatial analysis - Gymnastiar, Achmad Raihan; Ardasyah, Aksatria Krisna; Sawiji, Asri; Santoso, Eko Hadi (UIN Sunan Ampel Surabaya, 2026)
Jepara Regency, located on the northern coast of Central Java, Indonesia, with a coastline of approximately 82.72 km, has experienced significant topographic changes driven by natural processes and anthropogenic activities. These changes, combined with increasing rainfall variability, have heightened flood risk in several parts of the region. This study aims to analyze topographic changes between 2014 and 2023 and to assess flood risk by integrating rainfall intensity and slope characteristics using a GIS-based multi-criteria spatial analysis approach. This research utilizes secondary spatial and climatological data. Rainfall data for the period 2020–2022 were obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG) and classified according to rainfall intensity levels. Topographic and slope data were derived from the National Digital Elevation Model (DEMNAS) and the Indonesian Topographic Map (RBI). The analysis involved slope classification, scoring, weighting, and weighted overlay techniques using Geographic Information System (GIS) tools implemented in ArcMap software. The results indicate pronounced seasonal rainfall variability in Jepara Regency, with the lowest rainfall intensity occurring in July and the highest intensities recorded between December and January, ranging from 10.45 to 85.91 mm/day. Topographic analysis shows that areas with moderate slopes (8–15%) are vulnerable to extreme weather events and potential slope instability, while flat areas with slopes of 0–1% exhibit high susceptibility to flooding due to limited surface runoff capacity and land-use conditions. The total flood-prone area identified covers approximately 686.6 ha. Overall, the integration of rainfall and topographic parameters through GIS-based multi-criteria spatial analysis proves effective in identifying flood-risk zones and provides valuable input for spatial planning, disaster risk reduction, and coastal management in Jepara Regency.